AB0580 The effect of anti-tnf treatment in psoriatic arthritis patients treated in an ordinary clinical practice. (23rd January 2014) - Haugeberg, G.; Gulati, A. M.; Diamantopoulos, A. P.; Gabrielsen, K. H.; Hoff, M.; Kavanaugh, A.
Abstract : Background: Treatment with anti-TNF drugs in psoriasis arthritis (PsA) have in several randomized studies shown to have a favorable effect by reducing signs and symptoms and reducing the rate of radiographic progression (ref.1, 2 ). However real life data obtained from clinical practice is more scarce. Objectives: To explore in an ordinary rheumatology clinic the effect of anti-TNF treatment in PsA. Methods: The PsA patients were recruited from an ordinary rheumatology clinic located in the most southern part of Norway. The PsA patients are monitored using outcome measures and data is primarily registered for benchmarking in a clinical hospital computer database. Data collected for structured follow up and monitoring includes demographics, measures for disease activity, health status and treatment registration. Anonymised data was analyzed using SPSS. Results: Mean (SD) age for the 148 (men 84, women 64) anti-TNF treated PsA patients was 52.7 (11.0) yrs. Among them 72 had tried only one, 54 had tried 1 and 2 and 22 patients had tried 1, 2, 3 or more anti-TNF drugs. First anti-TNF treatment, sequence 1 (seq.1) was in median (IQR) used for 24 (43), seq.2 was used for 7 (24) and seq.3 or more for 9 (16) months. In the table mean baseline and last visit data for anti-TNF treatment is shown for seq.1, 2, and 3. Conclusions: Our real life data shows that when anti-TNF treatment is used for the first time in PsA the effect is better than when an anti-TNF drug is used for the second or third time. The clinical implication is that treatment effect diminishes with increasing number of TNF inhibitors used. References: Mease P et al. Arthritis Rheum 2004;50:2264-72. Kavanaugh A et al. ARD 2007;66:498-505 Disclosure of Interest: G. Haugeberg Shareholder of: in and founder of DiaGraphIT selling the computer tool GoTreatIT, Grant/research support from: Unrestricted research grant from Pfizer, A. Gulati: None Declared, A. Diamantopoulos: None Declared, K. Gabrielsen: None Declared, M. Hoff: None Declared, A. Kavanaugh: None Declared